RUNX1-dependent RAG1 deposition instigates human TCR-δ locus rearrangement - Cieslak, Agata; Le Noir, Sandrine; Trinquand, Amélie; Lhermitte, Ludovic; Franchini, Don-Marc; Villarese, Patrick; Gon, Stéphanie; Bond, Jonathan; Simonin, Mathieu; Vanhille, Laurent; Vanhile, Laurent; Reimann, Christian; et al. (The Journal of experimental medicine, 2014)
V(D)J recombination of TCR loci is regulated by chromatin accessibility to RAG1/2 proteins, rendering RAG1/2 targeting a potentially important regulator of lymphoid differentiation. We show that within the human TCR-α/δ locus, Dδ2-Dδ3 rearrangements occur at a very immature thymic, CD34(+)/CD1a(-)/CD7(+dim) stage, before Dδ2(Dδ3)-Jδ1 rearrangements. These strictly ordered rearrangements are regulated by mechanisms acting beyond chromatin accessibility. Importantly, direct Dδ2-Jδ1 rearrangements are prohibited by a B12/23 restriction and ordered human TCR-δ gene assembly requires RUNX1 protein, which binds to the Dδ2-23RSS, interacts with RAG1, and enhances RAG1 deposition at this site. This RUNX1-mediated V(D)J recombinase targeting imposes the use of two Dδ gene segments in human TCR-δ chains. Absence of this RUNX1 binding site in the homologous mouse Dδ1-23RSS provides a molecular explanation for the lack of ordered TCR-δ gene assembly in mice and may underlie differences in early lymphoid differentiation between these species.